“Together we are better”: Professional learning networks for teachers - Trust, Torrey; Krutka, Daniel G.; Carpenter, Jeffrey Paul (Computers & Education, 2016)
In recent years, many educators have turned to professional learning networks (PLNs) to grow in their craft with peers who are more accessible online because of reduced temporal and spatial constraints. While educators have cultivated PLNs, there is a dearth of research about the effects of PLNs. This manuscript reports the findings of a qualitative study that investigated PLN experiences through the analysis of survey data from 732 P-12 teachers. Data analysis suggests that the anytime, anywhere availability of expansive PLNs, and their capacity to respond to educators’ diverse interests and needs, appear to offer possibilities for supporting the professional growth of whole teachers. These findings have implications for defining the present and future of teacher learning in a digital age.
Keywords: Computer-mediated communication; Learning communities; Lifelong learning; PLN; Professional development